One dead spy : the life, times, and last words of Nathan Hale, America's most famous spy - Hale, Nathan, 1976- (New York : Amulet Books, 2012)
Nathan Hale, the author's historical namesake, was America's first spy, a Revolutionary War hero who famously said "I only regret that I have but one life to lose for my country" before being hanged by the British. In the Nathan Hale's Hazardous Tales series, author Nathan Hale channels his namesake to present history's roughest, toughest, and craziest stories in the graphic novel format.
Map illustrations on endpapers.
Includes bibliographical references (p. 118).
GN270L
3-6
2.6
Keywords: Hale, Nathan, -- 1755-1776 -- Comic books, strips, etc; Hale, Nathan, -- 1755-1776 -- Juvenile literature; Soldiers -- United States -- Biography -- Comic books, strips, etc; Soldiers -- United States -- Biography -- Juvenile literature; Spies -- United States -- Biography -- Comic books, strips, etc; Spies -- United States -- Biography -- Juvenile literature; Soldiers -- United States -- Biography; Spies -- United States -- Biography; Graphic nonfiction; United States -- History -- Revolution, 1775-1783 -- Secret service -- Comic books, strips, etc; United States -- History -- Revolution, 1775-1783 -- Secret service -- Juvenile literature; United States -- History -- Revolution, 1775-1783 -- Secret service; Comic books, strips, etc; Biographies; Graphic novels